Why What they Say Matters: The Impacts of Visitors’ Experiences on Tourism Sustainability - Adi Suryani; Soedarso Soedarso; Deti Rahmawati; Endarko Endarko; Ahmad Muklason; Berto Mulia Wibawa (Universitas Pendidikan Ganesha, 2021)
The success and failure of a destination tend to rest on its’ capacity to satisfy the visitors. Listening to visitors’ appraisal and voices is vital in community-based tourism development. This study aims to explore WPP Dalegan visitors’ voices. The data are collected through Dalegan visitors’ online reviews and direct observation. The study finds that Dalegan has a high competitive advantage as family recreational destination as it is cheap, reachable, accessible, has various local-traditional-cheap food, beautiful calm beach and soft white sand as a playing and learning ground for children. Despite its’ comfortable image, some visitors voice unsatisfied services, facilities, nature-caused and human-caused threats. The study also illuminates that Dalegan destination branding is not only influenced by its’ capacity to attract visitors by its’ beautiful marine nature, but also local community characters, community education and values. The study indicates that to develop tourism destination, local potentials are not the only determinant keys. It needs to be supported by other determining factors. One of those factors is tourists’ voices on their impression, comments, satisfaction and dissatisfaction feelings. Linking potential resources of destination and tourists’ meaningful experience can be challenging as different tourists may have different perspectives, wants and satisfaction-dissatisfaction levels.